Optimizing file transfer response time using the loss-load curve congestion control mechanism. - Williamson, Carey L. (Computer communication review.)
Loss-load curves are a recently proposed feedback mechanism for rate-based congestion control in datagram computer networks. In the loss-load model, packet loss inside the network is a direct function of sender transmission rates, and senders have the responsibility of choosing their own transmission rate based on the loss-load tradeoff curve provided by the network. Earlier work has provided the mathematical basis for the loss-load model and provided preliminary simulation results demonstrating its responsiveness, fairness, and stability. The loss-load model works well for simple network environments where each source has many packets to transmit, and wishes to maximize raw throughput.In this paper, the applicability of loss-load curves is extended to senders with more general network traffic requirements, such as file transfer activities. In particular, the paper considers senders wishing to minimize the response time for a transfer of N packets. When N is small, a sender chooses a low transmission rate, to minimize the probability of packet loss. When N is large, a higher transmission rate is chosen to increase raw throughput. The loss-load curve mechanism provides necessary and sufficient information for senders at the edges of the network to choose a proper transmission rate based on their traffic requirements and the current network load.Simulation results show that the loss-load mechanism is effective in achieving high network utilization and minimizing response time for file transfers. The loss-load model also does a good job of providing equitable service to senders with different traffic workloads and different round trip times.